2017
DOI: 10.1007/s12253-016-0169-z
|View full text |Cite
|
Sign up to set email alerts
|

Co-Expression of Putative Cancer Stem Cell Markers CD44 and CD133 in Prostate Carcinomas

Abstract: Cancer stem cells (CSCs) are the main players of prostate tumorigenesis thus; characterization of CSCs can pave the way for understanding the early detection, drug resistance, metastasis and relapse. The current study was conducted to evaluate the expression level and clinical significance of the potential CSC markers CD44 and CD133 in a series of prostate tissues. One hundred and forty eight prostate tissues composed of prostate cancer (PCa), high-grade prostatic intraepithelial neoplasia (HGPIN), and benign … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(26 citation statements)
references
References 56 publications
1
23
0
Order By: Relevance
“…In similar context, Paula et al [ 66 ] reported ALDH1 + /CD44 + co-expressing cells in non-malignant and neoplastic breast tissues. Similarly, Kalantari et al [ 67 ] reported CD44 + /CD133 + co-expressing putative CSC markers in prostate carcinoma. Consistent with these studies, expression of various stem and CSC-specific markers such as OCT4, SSEA4, ALDH, CD117, CD133, CD44, CD24, and LGR5 in our study, suggests presence of various CSC populations with characteristics which may explain heterogeneity, aggressiveness and metastatic potential of ovarian cancer.…”
Section: Discussionmentioning
confidence: 85%
“…In similar context, Paula et al [ 66 ] reported ALDH1 + /CD44 + co-expressing cells in non-malignant and neoplastic breast tissues. Similarly, Kalantari et al [ 67 ] reported CD44 + /CD133 + co-expressing putative CSC markers in prostate carcinoma. Consistent with these studies, expression of various stem and CSC-specific markers such as OCT4, SSEA4, ALDH, CD117, CD133, CD44, CD24, and LGR5 in our study, suggests presence of various CSC populations with characteristics which may explain heterogeneity, aggressiveness and metastatic potential of ovarian cancer.…”
Section: Discussionmentioning
confidence: 85%
“…Cancer stem cells (CSC) are a subpopulation of tumor cells, with capabilities of self‐renewal and differentiation, have been reported to be involved in the development of cancer. In‐depth study of CSCs can aid in the early detection of cancer, drug resistance, metastasis, and recurrence . Identification of miRNA transcriptome analysis in breast cancer spheres with CSC characteristics suggests that certain miRNAs can be used as new potential biomarkers for breast CSC diagnosis and targeted therapy .…”
Section: Discussionmentioning
confidence: 99%
“…PCa cells express several stem cell biomarkers, such as LSD1, SOX2, CD44, and CD133. [28][29][30][31][32] LSD1 and its inhibitor have been reported to target CSC markers in several cancers. 33,34 Sehrawat et al showed that LSD1 promotes PCa cell survival by activating gene networks that regulate the stem cell phenotype.…”
Section: Discussionmentioning
confidence: 99%